выполните действия;

(y^2-2a)(2a+y^2)

(3x^2+x)^2

(2+m)^2(2-m)^2

разложите на множители:

4x^2y^2-9a^4

25a^2-(a+3)^2

27m^3+n^3

если ктото решит буду очень признателен

2

Ответы и объяснения

Лучший Ответ!
  • mayli
  • светило науки
2012-04-16T11:14:36+04:00

(y^2-2a)(2a+y^2)=(y^2-2a)(y^2+2a)=y^4-4a^2

(3x^2+x)^2=9x^4+6x^3+x^2

(2+m)^2(2-m)^2=((2+m)(2-m))^2=(4-m^2)^2=16-8m^2+m^4

 

4x^2y^2-9a^4=(2xy-3a^2)(2xy+3a^2)

25a^2-(a+3)^2=(5a-a-3)(5a+a+3)=(4a-3)(6a+3)

27m^3+n^3=(3m+n)(9m^2-3mn+n^2)

 

2012-04-16T11:24:47+04:00

выполните действия;

(y^2-2a)(2a+y^2) = y⁴-4a²

(3x^2+x)^2= 9x⁴+6x³+x²

(2+m)^2(2-m)^2=[(2+m)(2-m)]²=[4-m²]²=16-8m²+m⁴

разложите на множители:

4x^2y^2-9a^4=(2xy-3a²)(2xy+3a²)

25a^2-(a+3)^2=[5a-(a+3)][5a+a+3]=(4a-3)(6a+3)

27m^3+n^3=(3m+n)(9m²-3mn+n²)